2016
DOI: 10.1083/jcb.201604003
|View full text |Cite
|
Sign up to set email alerts
|

Membrane curvature in cell biology: An integration of molecular mechanisms

Abstract: Curving biological membranes establishes the complex architecture of the cell and mediates membrane traffic to control flux through subcellular compartments. Common molecular mechanisms for bending membranes are evident in different cell biological contexts across eukaryotic phyla. These mechanisms can be intrinsic to the membrane bilayer (either the lipid or protein components) or can be brought about by extrinsic factors, including the cytoskeleton. Here, we review examples of membrane curvature generation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
281
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(287 citation statements)
references
References 127 publications
2
281
4
Order By: Relevance
“…Spontaneous curvature of lipid bilayers can be produced by a variety of relatively well understood mechanisms 18,21,22 . In particular, the insertion of amphipathic α-helix into lipid bilayers is known to induce curvature and is involved in several neck formation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous curvature of lipid bilayers can be produced by a variety of relatively well understood mechanisms 18,21,22 . In particular, the insertion of amphipathic α-helix into lipid bilayers is known to induce curvature and is involved in several neck formation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this diversity, their formation is subject to biophysical constraints, and most often requires bending the membrane in the presence of compositional in-plane heterogeneities. These membranes heterogeneities can be produced in many ways, resulting in a preferred mean curvature known as the spontaneous curvature [18][19][20][21][22] . The mechanisms inducing spontaneous curvature on the membrane can broadly be classified into five categories: lipid asymmetry across the leaflets, hydrophobic insertion due to proteins, scaffolding due to proteins, oligomerization, and crowding due to proteins or other external moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Curvature can also be generated by insertion of proteins like caveolin into one monolayer or surface association of intrinsically curved proteins that belong to the Bin, Amphiphysin and Rvs families [81]. K2P channel gating is modulated by lipid composition [44, 82], and reconstituted Piezo channels in lipid vesicles were activated by LPC (positive curvature generator) addition to the cytoplasmic monolayer [52].…”
Section: Gsmtx4 Mechanism Of Inhibition and Modulation Of Piezo Vs K+mentioning
confidence: 99%
“…Understanding the molecular mechanisms of these interactions is, therefore, of great importance. In the recent past, many proteins have been identified that can remodel membranes by their interplay with various cellular membranes [4, 5]. These include protein families like BIN/Amphiphysin/Rvs (BAR) [68], Eps 15-homology [9, 10], epsin [11], synaptotagmins [12] and synucleins [1315].…”
Section: A Introductionmentioning
confidence: 99%
“…This mechanism arises from the expansion of the total area of one membrane leaflet compared to the other [4, 5, 18, 19, 24]. Using these and/or quite possibly other mechanisms such as molecular crowding of protein on membrane, partitioning of shaped transmembrane domains, and cytoskeleton-mediated ‘pulling and pushing’ of membrane, a variety of membrane morphologies like small vesicles, tubular structures, membrane protrusions and lipoprotein particles are generated and have been observed in vivo [4, 5, 18, 19, 24, 25]. Interestingly, a single protein, for example α-synuclein, can also generate different lipid morphologies in vitro , even by just modulating the protein-to-lipid ratio (Fig.…”
Section: A Introductionmentioning
confidence: 99%